Análise da resposta dinâmica de um sistema mecânico com amortecedor de massa passivo: um estudo experimental e numérico - Garbin, Nayane Lais Schran (2018)
Dynamic vibration control is fundamental in noise reduction and structural vibration caused by external loads. If the vibration is excessive it can compromise the physical integrity of the structure, through a fatigue failure or simply generate discomfort and interfere in the safety of people. One of the methods of dynamic control is through the use of dynamic neutralizers, which use concentrated parameters of mass, rigidity and damping capable of absorbing the vibrational energy of the main structure where they are positioned, using the possible configurations as the neutralizers of the type mass and spring, viscoelastic and pendulum, for example. This dissertation aimed at the analysis of the response of a mechanical system reduced to a structure of two degrees of freedom and modeled as a bar and spring system, having the dissipation of the vibration given by the use of a dynamic pendulum neutralizer. The system response was analyzed numerically by the analytical model and the Matlab implementation of the system motion equations and the experimental signals of the system response to a random initial displacement and the external harmonic excitation were measured, resulting in the analysis of the system in two situations in free vibration and forced vibration. Satisfactory percentages of reduction of bar vibration amplitude were observed using the pendulum and it was observed that both numerically and experimentally the pendulum was efficient and dampened the vibration of the model using the pendulum mass parameters of 0.121 kg and a length of with a reduction of the amplitude of vibration in the bar and the increase of the amplitude of vibration of the pendulum, in each case, in considerable and satisfactory percentages.